Occurrence and management of traumatic oral injuries acquired by professional boxers in Metro Manila - Mañugo, Daryl; Rebueno-Santos, Jessica K. (Adviser).
Boxing is a combat sport where many have taken as a profession. The main risk in this profession is common exposure to blunt force trauma to different parts of body especially the head that may result to traumatic injuries. This study aims to describe occurrence and management of common traumatic oral injuries acquired in boxing in Metro Manila. Methods: Thirty three boxers were chosen from a list obtained from the Games and Amusement Board Boxing and Other Contact Games Division through total enumeration. Participants were visited in their respective stable or gyms and asked to answer a survey questionnaire. The data gathered were then encoded in Microsoft Excel to create tables and figures. Results: According to the data, the prevalence of Traumatic Oral injury can be as high being obtained is oral laceration. All participants use mouthguards. Mouthguard use is divided between boil-and-bite having a 73% usage and custom fabricated mouthguards having 33% usage. No participants use stock mouthguard. There is no significant difference in the correlation of the use of different mouthguards and the occurrence of oral injuries. This may be due to the small sample size obtained in the study. Sixty-four percent (64%) of the participants know some first aid treatment of TOI. Gargling warm water with salt, application of povidone-iodine solution, application of ice (cold compress), application of mouthgel, taking NSAIDs and/or antibiotics (amoxicillin) were listed as first aid by the boxers. Only 15.38%^ sought treatment from doctors or dentists and 84.62% of the participants managed the injury on their own. Conclusion: There is a high occurrence (79%) of traumatic oral injury in the sport of boxing in Metro Manila and its most common form is oral laceration. Sixty-four percent (64%) of boxers know some first aid management of these injuries. Only 15% of the participants seek medical and/or dental treatment and most prefer to manage the injury on their own.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.